If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 187 + -6x = 6x + 7 Reorder the terms: 187 + -6x = 7 + 6x Solving 187 + -6x = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 187 + -6x + -6x = 7 + 6x + -6x Combine like terms: -6x + -6x = -12x 187 + -12x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 187 + -12x = 7 + 0 187 + -12x = 7 Add '-187' to each side of the equation. 187 + -187 + -12x = 7 + -187 Combine like terms: 187 + -187 = 0 0 + -12x = 7 + -187 -12x = 7 + -187 Combine like terms: 7 + -187 = -180 -12x = -180 Divide each side by '-12'. x = 15 Simplifying x = 15
| 140-6x=2x+20 | | 6x+8=64-2x | | -5x+4=2 | | 4x+71=10x+71 | | 9x+5=3x+23 | | 6=.24x | | 4w^2+5=-9w | | 5x+8=-104 | | 8x^2-34x+21=0 | | 6x^2+27x=0 | | 9x-10=4x+5whatisx | | 8(x+2)-3(x+5)=2(x-2) | | 3(8a-2)-3(2a+4)=0 | | 0=2x | | 5a-6=4(2a+3) | | 5x+10=-86-7x | | 11-9x=62-30x | | 182-6x=5x+17 | | 4x+9=-16-8x | | 4x^2+8x-21=0 | | 25x^2-20x+3=0 | | 25x^2+80x+61=0 | | 4-(15-2x)=3[2x-9-2(9-x)] | | 16x^2+22=40x | | 4x^2+20x-40=0 | | 10x+6y=30 | | x^2-11x=3 | | x^2-18x+8=0 | | 8x+2=50 | | 6x^2-11+3=0 | | 35x^2+103x+72=0 | | 7x-3=21-9 |